KEMAMPUAN PEDAGOGIK CALON GURU DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KETERAMPILAN PROSES SISWA MELALUI PEMBELAJARAN BERBASIS PRAKTIKUM - Sudargo, Fransisca; S., Soesy Asiah (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
The aim of this research is to develop practical based biology learning to enhancing science process skill and critical thinking of high school students. Four pre-service teachers involved in this study, in order to develop their performance in innovation and variation of their teaching skills. The method of the study was descriptive and the samples were taken in purposive ways. Results of this study showed that the mean of critical thinking of four schools students that were taught through free inquiry and guided inquiry approach are 70,78, 62,28, 60,53 and 73,17. The mean of science process skill that was taken through observation sheet on concept water pollution is 81,43% and through written test is 73%. On concept nervous system there were significant improvement (α=0.05) between pre-test (25%) and post-test (70,44%). On concept soil and air pollution, there was no significance different between the use of pictorial sheet and ordinary sheet. The mean of students’ achievement on concept water pollution is 80,80; on concept sensory system: 73,69; on concept nervous system: 65,7. But there was no significance different between the use of pictorial sheet (49,74) and ordinary practical sheet (47,6) to enhance students’ achievement on concept soil and air pollution.